Game theory and learning for wireless networks : fundamentals and applications - Lasaulce, Samson (Academic Press, 2011)
This is the first comprehensive tutorial on game theory and its application to wireless communications. The book starts with a guide to the essential principles of game theory relevant to the communications engineer, giving tools that can be used to develop applications in wireless communications. It explains how game theory models can be applied to distributed resource allocation in a perfect world. Having clarified how the models can be applied in principle, the book then gives practical implementation methods for the real world, showing how the models in the perfect world need to be adapted to real life situations which are far from perfect. The first tutorial style book that gives all the relevant theory, at the right level of rigour, for the wireless communications engineer Bridges the gap between theory and practice by giving examples and case studies showing how game theory can solve real world resource allocation problems Contains algorithms and techniques to implement game theory in wireless terminals.